50 Ebola epidemic in war-torn Eastern Democratic Republic of Congo 2018: Rapid assessment of knowledge, attitudes, and practices - Mian, Qaasim (Paediatr Child Health, 2019)
BACKGROUND: The 2014–2016 West Africa Ebola outbreak claimed over 11,000 lives. Misconceptions and high risk behaviours such as unsafe burial practices contributed to the spread of the virus. Another Ebola epidemic is currently spreading in Eastern DRC, a densely populated, active conflict zone with many internally displaced persons (IDPs). The current outbreak is also significant in its high proportion of pediatric cases in recent months, presenting new challenges in the management of this crisis. OBJECTIVES: Local data on the knowledge, attitudes, and practices from the area could inform public health messaging during the current unprecedented epidemic. Our objective was to assess local community members’ perceptions related to the current Ebola outbreak. DESIGN/METHODS: We surveyed 582 community members and conducted focus group discussions with key community informants from 4 to 17 August, 2018 in the municipalities of Mangina (outbreak epicenter), Béni, Butembo, and Komando (IDP camp) in Eastern DRC. RESULTS: Knowledge of Ebola transmission was high (>80% correctly identified body fluids and contact with a corpse as risk factors), as was affective response (90% “worried” about Ebola). Nonetheless, a small but significant minority expressed attitudes that could hamper control efforts: unwillingness to bring suspected family members to an Ebola treatment unit (17%), intention to hide sick family members from authorities (17%), intention to touch or wash the body of a family member who died of suspected Ebola (8%), and unwillingness to accept a trained burial team (10%). Qualitative data corroborated these findings, emphasizing strongly held cultural preferences to be near the dying and deceased, early eyewitness reports of social resistance to control efforts, and accounts of substantial impediments posed by armed militias. On the other hand, acceptance of the new vaccine was high (80% would accept vaccination for their family). CONCLUSION: Community engagement for safe and dignified burials and attention to social resistance to control efforts may be as important in Eastern DRC as they were in West Africa in 2014–2016. The new vaccine, if made available to the general public, would likely be widely accepted.